1985
DOI: 10.1002/app.1985.070300810
|View full text |Cite
|
Sign up to set email alerts
|

Molecular weight distribution control in a semibatch “living” anionic polymerization. I. Theoretical study

Abstract: SynopsisA method to produce homopolymers of preestablished molecular weight distribution (MWD), through "living" anionic polymerizations carried out in homogeneous semibatch reactors is proposed and theoretically justified. In the direct form of the technique, very fast reactions are assumed, and the monomer and "killing" agent feed flows are obtained from the knowledge of the desired MWD, the system spreading function, the total reaction time, the initial reaction volume, and the reagent concentrations. Alter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
12
0

Year Published

1988
1988
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(12 citation statements)
references
References 9 publications
0
12
0
Order By: Relevance
“…On this basis, a variety of methods for gaining synthetic control over polymer MWDs have been developed 15–46 . Although the majority of early methods only afforded control over the relative breadth of the MWD, a limited number for controlling the entire MWD have been reported.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…On this basis, a variety of methods for gaining synthetic control over polymer MWDs have been developed 15–46 . Although the majority of early methods only afforded control over the relative breadth of the MWD, a limited number for controlling the entire MWD have been reported.…”
Section: Introductionmentioning
confidence: 99%
“…Although the majority of early methods only afforded control over the relative breadth of the MWD, a limited number for controlling the entire MWD have been reported. For example, Meira and co‐workers were able to impart MWD shape control in the anionic polymerization of styrene by oscillating the feed rates of monomer and alkyllithium initiator in continuous‐flow reactors 16–18 . In another example, Aoshima and co‐workers took advantage of controlled termination in a cationic polymerization, wherein the polymerization solution was metered into a solution of deactivating agent using a syringe pump 19 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…One of the first attempts is by Meira and co-workers and involves tuning the MWD of an anionic polymerization through manipulating the mixing efficiency of the monomer and initiator streams in a tubular continuous flow reactor with limited experimental success. [14][15][16] A more successful similar strategy is developed recently by Frey and co-workers. 17 Other methods focusses on directly influencing the polymer growth kinetics through changes in temperature, addition of rate modifying reagents or temporal addition of initiator to adjust the shape and breadth of MWDs in radical, ring-opening and anionic polymerization.…”
Section: Introductionmentioning
confidence: 99%
“…The majority of these processes only give control over the relative breadth of the distribution; however, a limited number have taken a step toward changing MWD shape. Specifically, Meira and co-workers have demonstrated that variation of monomer and initiator flow rates in continuous flow reactors imparted partial control over MWD shape. Further, methods have been developed using pulsed initiation through photolysis or monomer/initiator feeds to give multimodal distributions. Additionally, Aoshima and co-workers have tuned polymer composition through controlled termination processes . Although these methods give partial control, new strategies are still needed to give precise regulation of MWD shape in living polymerization processes.…”
mentioning
confidence: 99%